Analysis and recommendations for business process improvement for retail companies using the business process improvement (BPI) method - Raihan, Ahmad; Kanza, Adam Satrio; Rohmah, Ahlam Umniyatur; Khairani, Dina Zhafira (Journal of Student Research Exploration, 2023)
Retail companies are businesses that involve direct interaction between sellers of goods or services and consumers, meaning that retail businesses do not have a processing process from raw materials to finished products. In the process of editing and recapping goods data, there are 2 main businesses, namely editing data, sending copies of goods data, and storing new data in the cashier’s GIS database. After the evaluation, it was found that simplification could be made to make it more efficient. Based on the results of the evaluation of the business process, it was found that the root cause of the editing time and recap of goods data was long. Business process recommendations are made and the results are obtained, eliminating the process of providing a copy of new item data to the warehouse clerk and storing new item data in the cashier’s GIS database.